A review on the huntsman spider genus Spariolenus Simon, 1880 (Araneae: Sparassidae: Heteropodinae) in Iran with description of four new species - Moradmand, Majid; Jäger, Peter (Zootaxa, 2011)
Four new species of the huntsman spider genus Spariolenus Simon, 1880 are described from Iran: S. aratta spec. nov. (female) from Jebal Barez mountains in Kerman Province, S. iranomaximus spec. nov. (male, female) from Khofash cave in Ilam Province, S. manesht spec. nov. (female) from Manesht mountain in Ilam and S. zagros spec. nov. (male, female) from Kenesht cave, Kermanshah Province. We present an extended diagnosis for the genus and information on the natural history of the new species. This is the first record of the subfamily Heteropodinae in Iran. Females of S. iranomaximus spec. nov. are larger than any spider ever found in the Middle East. All the species occurred in caves and rock crevices of the Zagros mountain range in Iran. According to the geographical distribution of currently known Spariolenus species, palaeontology perspectives and geological history of the area an evolutionary scenario of speciation associated with Zagros orogeny is proposed.